The Influence Of Children's Mother Class With Improving Mother's Knowledge About Balanced Nutrition In Toddlers At Posyandu Mawar X Kelurahan Adiarsa Barat Working Area Puskesmas Nagasari District Karawang - Astri Puji Rahayu; Nanik Yuliwati (Pusat Riset dan Inovasi Nasional, 2023)
Background : Toddlers are one of the groups that are prone to health problems, problems with malnutrition or malnutrition. During the toddler period this will occur a phase of growth and development which is very rapid. As for malnutrition in toddlers it doesn't happen suddenly, but begins with an increase in toddlers' body weight which is not enough. One of the government's programs to I deal with nutritional problems in toddlers that have been going on until now, namely by breastfeeding mothers of toddlers. Research Objectives : To find out the effect of breastfeeding on toddler mothers by increasing mothers' knowledge about balanced nutrition for toddlers at Posyandu Mawar X Kelurahan Adiarsa Barat Work Area at Nagasari Community Health Center, Karawang Regency. Research Methods : The type of research used in this study. quasi-experimental quasi-experimental with the design used was the pre and posttest approach twoi groupi design. The population in this study was 68 mothers of toddlers. Bivariate analysis using dependent t tests. Research results : Knowledge of mothers about balanced nutrition in toddlers before classiation mothers of toddlers in mothers in the intervention group mostly reduced by reducing by 11 people (73.3%) with an average score of 10.60, knowledge of mothers about balanced nutrition in toddlers before classiating mothers under five in the control group was mostly reduced by reducing by 8 people (53.3%) with an average score of 11.33. Mothers' knowledge of balanced nutrition in toddlers after classiation of mothers of toddlers in mothers in the intervention group mostly improved by 9 people (60.0%) with an average average score of 15.60, knowledge of mothers about balanced nutrition in toddlers after classiation mothers of toddlers in control groups mostly adequate by 8 people (53.3%) with a mean score of 13.53. Conclusion : It can be concluded that there is an influence on mother's toddlers by increasing mother's knowledge about balanced nutrition for toddlers in Posyandu Mawar X Kelurahan Adiarsa Barat Work Area at Nagasari Community Health Center, Karawang Regency.